APPLYING THINK-TALK-WRITE (TTW) IN THE TEACHING OF READING COMPREHENSION IN RELATION TO STUDENTS’ CRITICAL THINKING SKILLS - Imran, Fathurrahman; Firman, Edi; Raudhatunnisa, Sri (Journal of Languages and Language Teaching, 2019)
This research was aimed at finding out the effect of Think Talk Write (TTW) towards students’ critical thinking skills in reading comprehension at the first grade of SMKN 2 Lingsar. The research was experimental research. The design was quasi-experimental design by with nonequivalent control group design. The two classes were chosen as the samples in this research which consist of 32 students. They were chosen by using purposive sampling technique. The research instruments consist of reading tests and questionnaire. Reading test was employed in the form of a multiple choice and essay. Meanwhile, the questionnaire was used to attain the students’ critical thinking skills. In analyzing the data, researchers applied statistical analysis. It showed the value of t-test = 2,482 ≥ t-table = 1,697 at the significant level 5% (0.05). Based on the results of the analysis, it can be concluded that Think Talk Write has a positive effect on students' critical thinking in reading comprehension at first-grade student of SMKN 2 Lingsar. In other words, the alternative hypothesis (Ha) is accepted and null hypothesis (Ho) is rejected.